Adapting Scotland's forests to climate change using an action expiration chart. (21st October 2015) - Petr, M; Boerboom, L G J; Ray, D; van der Veen, A
Abstract: The inherent uncertainty of climate change impacts is one of the main challenges for adaptation in environmental management. The lack of knowledge about climate impacts on ecosystem services at high spatial and temporal resolution limits when and what adaptation measures should be taken. We addressed these limits by assessing four ecosystem services—forest production, tree growth, sequestered carbon, and tourism potential—under drought or climate change. To support adaptation, we adapted the existing concept of 'dynamic adaptive policy pathways' for forest management by developing an action expiration chart, which helps to define expiry dates for forestry actions using ecosystem services delivery thresholds. We assessed services for Sitka spruce, Scots pine, and pedunculate oak on the National Forest Estate in Scotland for the next 80 years using probabilistic climate change data from the UKCP09 weather generator. Findings showed that drought would have an overall long-term negative impact on the provision of three services with a decrease up to 41%, whereas climate change has a positive impact on tourism potential with up to five times higher frequency of good climate conditions during summer months. Furthermore, the results highlighted when forestry actions, mainly in the lowlands, will reach their environmental limits during the next 80 years. Our findings reduce knowledge uncertainty and highlight when and where adaptation should be implemented to ensure the provision of future forest ecosystem services in Scotland.